Enhancing Student Character: A Bibliometric Study on The Role of Local Wisdom Approaches - Abdul Salam; Agus Setiawan; Aminuddin Prahatama Putra; Yadi Ruyadi (Journal of Law and Bibliometrics Studies, 2026)
Objective: The present research aims to analyze the development, trends, and intellectual structure of research on the role of local wisdom approaches in character building among students through a bibliometric study. Method: Bibliometric analysis using Scopus-indexed publication data for the 2014–2024 period. Data were obtained through a search using the keywords "local wisdom" and "character", resulting in 87 documents that met the analysis criteria. Results: Data processing was carried out using Microsoft Excel for frequency analysis and descriptive statistics, and VOSviewer to map collaboration networks and keyword relationships. The results show that publications on local wisdom and character education experienced a significant upward trend, peaking in 2020. Indonesia had the highest number of publications, while Ganesha University of Education and I Wayan Suastra were the most productive institutions and authors, respectively. Keyword network analysis identified three main clusters: character education and learning, local culture-based character education, and character building through local wisdom. The findings also indicate that the integration of local culture into character education has become an increasingly dominant theme since 2021. The implications of this research emphasize the importance of using local wisdom values as a contextual character education strategy relevant to students' cultural identities. Novelty: Presentation of a comprehensive bibliometric mapping of the relationship between local wisdom and character education, while also identifying trends, key actors, and remaining research opportunities in this field.